Potential role of Plasmodium falciparum-derived ammonia in the pathogenesis of cerebral malaria - Kimoloi, Sammy; Rashid, Khalid (Frontiers in Neuroscience, 2015)
Cerebral malaria (CM) is the most severe complication associated with Plasmodium falciparum infection. The exact pathogenic mechanisms leading to the development CM remains poorly understood and the mortality rates remain high. Several potential mechanisms including mechanical obstruction of brain microvasculature, inflammation, oxidative stress and hemostatic dysfunction have been suggested to play a role in CM pathogenesis. However, these proposed mechanisms, even when considered together, do not fully explain the pathogenesis and clinicopathological features of human CM. This necessitates consideration of alternative pathogenic mechanisms. P. falciparum generates substantial amounts of ammonia as a catabolic byproduct, but lacks detoxification mechanisms. Whether or not this parasite-derived ammonia plays a pathogenic role in CM is yet to be considered, despite its potential to cause localized brain ammonia elevation and subsequent neurotoxic effects. This article therefore, explores and proposes a potential role of parasite-derived ammonia in the pathogenesis and neuropathology of CM. A consideration of parasite-derived ammonia as a factor in CM pathogenesis provides plausible explanations of the various features observed in CM patients including how a largely intravascular parasite can cause neuronal dysfunction. It also provides a framework for rational development and testing of novel drugs targeting parasite’s ammonia handling.